Mechanisms of time‐dependent deformation in porous limestone. Issue 7 (25th July 2014) - Brantut, Nicolas; Heap, Michael J.; Baud, Patrick; Meredith, Philip G.
Abstract We performed triaxial deformation experiments on a water‐saturated porous limestone under constant strain rate and constant stress (creep) conditions. The tests were conducted at room temperature and at low effective pressures Peff=10 and Peff=20 MPa, in a regime where the rock is nominally brittle when tested at a constant strain rate of 10−5 s−1. Under these conditions and at constant stress, the phenomenon of brittle creep occurs. At Peff=10 MPa, brittle creep follows similar trends as those observed in other rock types (e.g., sandstones and granites): only small strains are accumulated before failure, and damage accumulation with increasing strain (as monitored by P wave speeds measurements during the tests) is not strongly dependent on the applied stresses. At Peff=20 MPa, brittle creep is also macroscopically observed, but when the creep strain rate is lower than ≈10−7 s−1, we observe that (1) much larger strains are accumulated, (2) less damage is accumulated with increasing strain, and (3) the deformation tends to be more compactant. These observations can be understood by considering that another deformation mechanism, different from crack growth, is active at low strain rates. We explore this possibility by constructing a deformation mechanism map that includes both subcritical crack growth and pressure solution creep processes; the increasing contribution of pressure solution creep at low strain rates is consistent with our observations.